STRENGTHENING CHARACTER BUILDING TO INCREASE THE PERSONAL COMPETENCY OF TEACHERS AT SMK BUDI PERKASA - Salmah, Salmah; Rahmi, Amelia; Andria, Fredi (Yayasan Education and Social Center, 2024)
SDM is the most important asset for building a more advanced nation. However, to achieve that, human resources must have character. Teachers must be qualified and have strong character to have resources with character. A good teacher will always be a role model for his students. SMK Budi Perkasa is a vocational high school that faces the problem of weak personal competence possessed by teachers; we can see from the way teachers communicate with less professional students, lack of openness in thinking and acting, lack of teacher ability in developing positive character in behavior which can have a positive influence on student behavior and foster respected behavior, as well as a lack of maturity in relationships between fellow teachers at work. This Community Service Activity (PKM) is carried out to solve several problems partners face by providing character strengthening to teachers. It aims to foster better and more professional attitudes and behavior from teachers in carrying out their duties as educators and also to improve the personal competence of teachers. The forms of PKM implemented are Effective Communication Skills Training, Grooming, and Character Building strengthening training